EFFECT OF FIXED ORTHODONTIC TREATMENT BY UNLICENSED DENTAL SERVICE ON DENTAL HEALTH - Rahmadaniah Khaerunnisa; Lisna Wati Solihat (Fakultas Kedokteran Gigi Unjani, 2022)
Orthodontic treatment is a treatment that induces light pressure on the teeth by using an orthodontic appliance so that the teeth move in a determined direction. Fixed orthodontic treatment must be following the instructions of an orthodontist however many unlicensed dental services and online shop sites offer free braces. Side effects can occur in patients with a fixed orthodontic appliance, but this has been minimized by dentists in the treatment process so that patients get greater benefits. Fixed orthodontic treatment by unlicensed dental services is done without any responsibility in case of an error that threatens dental health. It was reported that 22 years old woman complained that her lower anterior teeth were mobile and there was a white spot on the part where the bracket was set up. The patient wanted to remove the braces that were attached by the unlicensed dental services several years ago. Patients diagnosed with periodontitis localized of teeth 32-42 with mobility grade II et causa trauma of fixed orthodontic appliances. The dental emergencies of tooth mobility, in this case, were carried out by orthodontic bracket removal on the upper and lower teeth and followed by periodontal treatment. So that it does not cause further damage to the underlying supporting tissue and cause the tooth to extrude. DOI : 10.54052/jhds.v2n1.p63-74